Example 3 - Chapter 2 Class 12 Inverse Trigonometric Functions - Part 3

Example 3 - Chapter 2 Class 12 Inverse Trigonometric Functions - Part 4

  1. Chapter 2 Class 12 Inverse Trigonometric Functions (Term 1)
  2. Serial order wise

Transcript

Example 3 Show that (ii) sin−1 (2x√(1−𝑥2)) = 2 cos−1x Solving L.H.S. sin−1 ( 2x √(1−𝑥2) ) Putting x = cos θ = sin−1 ("2 cos θ " √(𝟏−𝒄𝒐𝒔𝟐" θ" )) = sin−1 ("2 cos θ " √(𝒔𝒊𝒏𝟐" θ" )) = sin−1 (2 cos θ sin θ) = sin−1 (sin 2θ) We need to make 2x √(𝟏−𝒙𝟐) in terms of sin When we get √(1−𝑥2) , we put x = cos θ or sin θ = 2θ = 2 × cos−1 x = 2 cos−1 x = R.H.S. Since L.H.S. = R. H. S. Hence proved As x = cos θ cos−1 x = θ

About the Author

Davneet Singh's photo - Teacher, Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.